Epidemiology, Risk Factors and Measures to Combat Diseases Caused by Klebsiella Bacteria - qizi, Muminova Madinakhon Abdulkhaq; qizi, Kalandarova Matluba Khuzhaniyoz; ugli, Nazarov Uktam Usmon (American Journal of Bioscience and Clinical Integrity, 2024)
Infections caused by klebsiella species occur in various places such as the circulatory system, wounds or surgical incisions, lungs, urinary tract and brain. People with pre-existing diseases are more likely to be exposed to these infections. Due to the growing number of carbapenem-resistant and extremely virulent strains, K. pneumoniae has become a serious pathogen of international concern. It is extremely important to have an understanding of the risk factors, methods of prevention and methods of treatment of infections caused by klebsiella resistant to a variety of drugs. K. pneumoniae is a dangerous nosocomial pathogen that often causes nosocomial outbreaks and demonstrates varying virulence and sensitivity to antibiotics. Medical institutions must identify bacterial factors that are crucial during infection, due to the occurrence of many intractable infections caused by K. pneumoniae. We investigated the presence of virulence genes in several isolates obtained from urinary tract infections, respiratory tract infections, blood, wounds, and colonization of the digestive tract to better understand this diverse pathogen. In this article, we review the epidemiology, risk factors, and methods of controlling infections caused by K. pneumoniae to highlight the serious threat posed by this pathogen, as well as existing treatments for diseases caused by klebsiella. Identification of virulence factors in K. isolates pneumoniae, especially in combination with antibiotic resistance, is very important because it allows you to assess the possible course and localization of infection in the human body and is necessary to develop a treatment strategy.